Cultivating Fandom: An Analysis of GMMTV's Marketing Communication Strategy for Southeast Asian Audiences in "My School President” Series - Purbantina, Adiasri Putri; Prakoso, Doddy Agus; Alexandra, Renya Dominique; Zardi, Jihan Putri Rindra; Tarunajaya, Muhammad Raihan (Jurnal Komunikasi Nusantara, 2025)
"My School President", a TV series by GMMTV has gained global popularity, particularly among the Southeast Asian markets. This research analyzes GMMTV's marketing communication strategy (IMC) to promote the "My School President" series in the Southeast Asian market from 2022 to 2023. In this research, we use a qualitative case study method to evaluate five components of IMC: (1) advertising, (2) sales promotion, (3) personal selling, (4) public relations, and (5) direct digital marketing. In addition, we incorporate K-pop marketing style into our IMC indicators. We use relevant secondary data, such as GMMTV's official social media, annual report, journal, news, and engagement data from the "My School President" series, to evaluate GMMTV's strategy in marketing the series in the Southeast Asian market. We find similarities between GMMTV's approach and the K-Pop industry's strategy in marketing their creative products. Abstrak “My School President” merupakan serial produksi GMMTV yang berhasil mendapatkan popularitas tinggi di pasar domestik maupun Asia Tenggara. Penelitian ini bertujuan untuk menganalisis strategi komunikasi pemasaran GMMTV dalam mempromosikan serial “My School President” di pasar Asia Tenggara tahun 2022-2023. Konsep yang digunakan dalam penelitian ini yaitu Integrated Marketing Communication oleh Kotler dan Armstrong (2018) yang terdiri dari lima komponen, meliputi: (1) advertising; (2) sales promotion; (3) personal selling; (4) public relation; dan (5) direct digital marketing. Penelitian ini menggunakan metode deskriptif kualitatif, dengan pendekatan studi kasus berdasarkan acuan data sekunder yang relevan, seperti: (1) media sosial resmi GMMTV; (2) annual report; (3) jurnal; (3) berita; dan (5) data engagement dari serial “My School President”. Hasil dari penelitian ini menunjukkan bahwa strategi komunikasi pemasaran yang diterapkan GMMTV dalam promosi serial “My School President” memiliki kesamaan dengan strategi industri K-Pop dalam memasarkan produk kreatif. GMMTV juga menerapkan lima komponen dari Integrated Marketing Communication dalam promosi serial “My School President” melalui pemanfaatan media sosial, engagement, penjualan produk merchandise, dan pagelaran event untuk memperoleh profit yang maksimal pada pasar Asia Tenggara.